Cover Image. Issue 7 (15th October 2019) - Gentileschi, Stefano; Albanese, Roberta; Pino, Valentina; Stefanizzi, Gianluigi; Fragomeni, Simona; Zagaria, Luca; Ieria, Francesco P.; Salgarello, Marzia; Scambia, Giovanni; Garganese, Giorgia
Abstract : The cover image is based on the Clinical Article SPECT/CT and fusion ultrasound to target the efferent groin lymph node for lymphatic surgery by Stefano Gentileschi MD et al., DOI:https://doi.org/10.1002/micr.30501 .